PREGNANCY AND DELIVERY OUTCOMES IN PREECLAMPSIA WITH OBESITY - Kattakhodjaeva , M.Kh.; Gaybullaeva , D.F. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Obesity in pregnant women is considered as a risk factor for the development of severe forms of hypertensive conditions in pregnant women during pregnancy. The incidence of preeclampsia in obese women is approximately three times higher than in women with normal body weight, and reaches 78% according to various studies. The aim of the study was to evaluate the characteristics of the course of pregnancy, childbirth and the postpartum period in women with preeclampsia and obesity. 133 pregnant women with preeclampsia and obesity were examined. The following metabolic indices were studied: concentration of total protein, total cholesterol, creatinine, the content of glucose, urea, total bilirubin and direct bilirubin, serum iron, fibrinogen, beta-lipoproteins, alanine aminotransferase activity, aspartate aminotransferase activity; the prothrombin index in blood serum, clinical blood test parameters in pregnancy dynamics were determined. The results showed an earlier onset of preeclampsia, high blood pressure levels. The higher the woman’s BMI, the lower the newborn’s Apgar score (6.25±0.75 points - with a mother’s BMI of 35 or more; 6.35±0.42 points - with a BMI of 30-34.9; 6.86±0.11 points - with normal body weight, p<0.001). It should be noted that cholesterol, lipoproteins, and increased fibrinogen levels in themselves have proatherogenic, proinflammatory, and procoagulant effects, which contributes to the development of preeclampsia.